FAKTOR-FAKTOR YANG MEMPENGARUHI AGRESIVITAS PAJAK PADA PERUSAHAAN SEKTOR INDUSTRIAL - Andrew Van Breeman; Yuniarwati Yuniarwati (Jurnal Paradigma Akuntansi, 2026)
This research was conducted with the aim to determine the effect of leverage, liquidity, capital intensity on tax aggressiveness. The population used in this study are industrial sector companies listed on the Indonesia Stock Exchange during 2019-2021. In selecting the sample in this study using a purposive sampling method and obtained as many as 40 sample companies. In this study, the data processing technique used is logistic regression analysis and uses the IBM SPSS Statistics application version 25. The results of this study indicate that leverage and liquidity have no significant effect on tax aggressiveness, and capital intensity has a significant effect on tax aggressiveness.